Design, synthesis and evaluation of novel N-phenylbutanamide derivatives as KCNQ openers for the treatment of epilepsy. Issue 17 (15th September 2018) - Yang, Shaoning; Lu, Dingqiang; Ouyang, Pingkai
Graphical abstract: Highlights: A series of novel N -phenylbutanamide derivatives as KCNQ openers for treatment of epilepsy were investigated. KCNQ opening activity was evaluated in vitro and in vivo . Compound 1 was found to possess significant anti-convulsant activity with good safety profile and pharmacokinetic property. Abstract: KCNQ (Kv7) has emerged as a validated target for the development of novel anti-epileptic drugs. In this paper, a series of novel N -phenylbutanamide derivatives were designed, synthesized and evaluated as KCNQ openers for the treatment of epilepsy. These compounds were evaluated for their KCNQ opening activity in vitro and in vivo . Several compounds were found to be potent KCNQ openers. Compound 1 with favorable in vitro activity was submitted to evaluation in vivo . Results showed that compound 1 owned significant anti-convulsant activity with no adverse effects. It was also found to posses favorable pharmacokinetic profiles in rat. This research may provide novel potent compounds for the discovery of KCNQ openers in treating epilepsy.